Uma Avaliação de técnicas e Critérios de Teste de Software para a Linguagem de Programação Python - Oliveira Brito, Renata (2022)
Python programming language has gained ground in the software industry and has become one of the most popular programming languages, due to its simplicity and flexibility, which facilitates learning, in addition to popularizing the use of new computing technologies, such as machine learning. Considering this scenario, this work explores this problem by categorizing and evaluating software testing techniques and criteria applied to the Python programming language. Among the activities developed, it is worth highlighting an assessment regarding the ability to apply the testing techniques context of Python, categorization of tools and technologies that support the application of such approaches, as well as the development of a practical study to measure the feasibility of applying them in the context of open-source projects.